Authoritarianism and Violence: An Arendtian Critique of the Philippine War on Illegal Drugs - Ullero, Janflor Mc.Louie (PT FORMOSA CENDEKIA GLOBAL, 2025)
The Philippine War on Drugs, initiated under President Rodrigo Duterte’s administration, has been marked by authoritarian governance and widespread violence, particularly through extrajudicial killings (EJKs). This paper critically examines the authoritarian dimensions of the drug war through the lens of Hannah Arendt’s political philosophy, particularly her analyses of power, violence, and the “banality of evil.” Arendt warns that authoritarianism thrives on coercion and the erosion of public discourse, often justifying state violence as a means to maintain order. The normalization of EJKs in the Philippines exemplifies how authoritarian tendencies undermine democratic institutions and the rule of law. Applying Arendt’s critique, this study explores how the drug war fosters a culture of unthinking obedience among state actors and desensitization among the public. Arendt’s concept of the “banality of evil” suggests that perpetrators of state-sponsored violence do not necessarily act out of malice but rather from an uncritical acceptance of authority and policy. By examining the mechanisms through which authoritarian rule legitimizes violence, this paper argues that the Philippine War on Drugs reflects a dangerous collapse of political deliberation, wherein fear replaces reasoned debate. Ultimately, this paper calls for a reinvigoration of public discourse and critical thinking as a means of resisting authoritarian violence. An Arendtian critique highlights the necessity of political engagement, moral responsibility, and institutional accountability in preserving democratic values against the excesses of authoritarian rule.